Association between lactate dehydrogenase levels and all-cause mortality in ICU patients with heart failure: a retrospective analysis of the MIMIC-IV database - Panxu Guo; Hongfu Ding; Xiaowan Li; Danying Xie; Ke Wang; Wanmin Su; XiaoJuan Yang; Fang Nie; Peixi Wang (BMC Cardiovascular Disorders)
Abstract Background Heart failure (HF) patients admitted to the intensive care unit (ICU) often face high short-term mortality rates. This study aims to investigate the relationship between lactate dehydrogenase (LDH) levels and all-cause mortality in critically ill patients with HF. Methods Data from the MIMIC-IV database were extracted for subjects eligible for HF diagnosis. We utilized the restricted cubic spline (RCS) method, Kaplan-Meier (K-M) survival curves, and Cox regression analysis to assess the association between lactate dehydrogenase (LDH) levels and all-cause mortality in HF patients. Overlap weighting (OW) and subgroup analysis were employed to enhance the robustness and reliability of the study. Results A total of 3,065 subjects were enrolled in this study. RCS analysis revealed a nonlinear relationship between LDH levels and the risk of all-cause mortality in critically ill patients with HF, with a hazard ratio (HR) > 1 when LDH exceeded 315 U/L. The K-M survival curve indicated lower survival rates and shorter survival times in subjects with LDH ≥ 315 U/L. Elevated LDH levels were independently associated with increased in-hospital and 1-year mortality rates, with adjusted HR of 1.39 (95% CI: 1.16, 1.67) and 1.29 (95% CI: 1.14, 1.45), respectively. The results remained consistently robust in the OW analyses. Conclusions Elevated LDH levels were significantly associated with an increased risk of all-cause mortality in ICU-admitted HF patients. Further randomized trials are needed to confirm this association.